Analysis of modern condition ofpurebredcattle in program «Sybaga» of Republic of Kazakhstan. - Aidarova, A. B.; Esentaeva А. А.; Dosmuratova, E. E. (Journal of Economic Research & Business Administration, 2015)
This article examines the implementation of the program «Sybaga» the purpose of which is to ensure increase the number commodity herd of cattle a meat direction that enters in the program «Development of export potential of cattle» in the meat direction, to ensure population with quality meat products, transformation pedigree cattle by crossing mongrel brood stock and breeding bulls of beef productivity, reduce the cost of meat, the opening of additional jobs